THE USE OF FIGHTS AS A THEMATIC AXIS BY PHYSICAL EDUCATION TEACHERS/PROFESSORS OF THE MUNICIPAL NET OF TEACHING IN DOURADOS/MS (Fiep Bulletin - online, 2016)
Investigate the use of fights as thematic axis by physical education teachers of the municipal net of teaching in Dourados/MS. It was a qualitative, quantitative and transversal field research, having a descriptive character. The population was formed by 37 teachers/professors, both genders, between 25 and 40 years old, professionals who act in the Municipal net of teaching in Dourados/MS, being accomplished in 14 out of 26 municipal schools of Dourados/MS chosen through simple and casual draw, contemplating all the regions of the city. The results have expressed that most of the professionals resorts in anyway to the theme as practice of their classes. From 37 professionals questioned, 23 (62,16%) have affirmed the practice of fights in their classes and 11 (29,72%) have said that they do not use this content as theme in their classes, and still 03 (0,81%) have opted not to answer this question. It is possible to conclude that Physical Education cannot provide such different ways of body culture indicated by the Curricular National Parameters, being required an update and study of the theme related, among them the fights, and also making use of creativity in possible alternatives in this area.
Keywords: Scholar Physical Education. Fights. Contents.